2018
DOI: 10.3390/e20090664
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Mixed Convection and Entropy Generation in a Wavy-Walled Cavity Filled with Nanofluid and Involving a Rotating Cylinder

Abstract: This numerical study considers the mixed convection and the inherent entropy generated in Al 2 O 3 –water nanofluid filling a cavity containing a rotating conductive cylinder. The vertical walls of the cavity are wavy and are cooled isothermally. The horizontal walls are thermally insulated, except for a heat source segment located at the bottom wall. The dimensionless governing equations subject to the selected boundary conditions are solved numerically using the Galerkin finite-element method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 61 publications
3
28
0
Order By: Relevance
“…They found that undulations on the cold wall improve the heat transfer rate. Considering the wavy wall forms, the entropy generation [22,23], non-uniform heating [24], partially heated wall [25,26], and micropolar fluids [27] have been investigated in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…They found that undulations on the cold wall improve the heat transfer rate. Considering the wavy wall forms, the entropy generation [22,23], non-uniform heating [24], partially heated wall [25,26], and micropolar fluids [27] have been investigated in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The entropy generation is expressed by two quantities, i.e., heat transfer (first term in below equation) and liquid friction (last term in below equation) [18,21,22,34].…”
Section: Entropy Generationmentioning
confidence: 99%
“…Nanofluids are pioneering fluids in the field of thermal science and it has been used actively to analyze the energy transport in thermal systems [16][17][18][19][20][21][22]. Sheremet et al [21] discovered the buoyant flow and entropy generation of nanoliquid in a closed box with variable border temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an essential aspect of the 2nd law of thermodynamics [ 21 , 22 ]. The study of entropy generation in closed domain has been analyzed in several studies [ 23 , 24 , 25 ]. Ahmed et al [ 26 ] analyzed the entropy production due to doubly diffusive convection of Casson liquids in the occurrence of slip boundaries and chemical reactions.…”
Section: Introductionmentioning
confidence: 99%